Measurement of the CP asymmetry in B0s-B[bar]0s mixing - Aaij, Roel; D'Argent, Philippe; Bachmann, Sebastian; Braun, Svende; Britsch, Markward; Comerma-Montells, Albert; De Cian, Michel; Esen, Sevda; Gerick, David; Gersabeck, Evelina; Han, Xiaoxue; Hansmann-Menzemer, Stephanie; et al. (Physical review letters, 2016)
The CP asymmetry in the mixing of B0s and ¯B0s mesons is measured in proton-proton collision data corresponding to an integrated luminosity of 3.0 fb−1, recorded by the LHCb experiment at center-of-mass energies of 7 and 8 TeV. Semileptonic B0s and ¯B0s decays are studied in the inclusive mode D∓sμ±(−)νμX with the D∓s mesons reconstructed in the K+K−π∓ final state. Correcting the observed charge asymmetry for detection and background effects, the CP asymmetry is found to be assl=(0.39±0.26±0.20)%, where the first uncertainty is statistical and the second systematic. This is the most precise measurement of assl to date. It is consistent with the prediction from the standard model and will constrain new models of particle physics.